THE EFFECT OF LIQUID ASSETS RATIO AND NON PERFORMING LOANS ON THE PROFITABILITY OF COMMERCIAL BANKS IN INDONESIA - Anandita, Ribkah; Laba, Abd. Rakhman; Aswan, Andi (Accounting Profession Journal (APAJI), 2024)
The aim of this study was to investigate the relationship between the Liquid Assets Ratio (LAR) and Non-Performing Loans (NPL) variables and the profitability of Indonesian Commercial Banks as measured by Non-Performing Loans (NPL) and Return on Asset (ROA). The study's observational term, from 2013 to 2022, spans 10 years. The Financial Services Authority (OJK) financial statements are where the study's data was derived from. The data analysis technique employed Multiple linear regression is the approach of data analysis that is used. The data is first checked with traditional assumption tests, such as normality, heteroscedasticity, multicollinearity, and autocorrelation tests, before employing this method. The findings demonstrated that the LAR variable has no appreciable impact on the profitability of Indonesian commercial banks. The NPL variable exhibits a large influence on the profitability of commercial banks in Indonesia, whereas the former has a negligible impact. In this study, the independent variables can account for up to 89.7% of the variation in the dependent variable, with the remaining variation being impacted by other variables.